ANALISA EFEKTIFITAS JEMBATAN PENYEBERANGAN ORANG (JPO) DI KOTA SAMARINDA (Studi Kasus Ruas Jalan Ir. H. Juanda Samarinda) - FAHRIANI, NURLISA (KURVA S JURNAL MAHASISWA, 2018)
Nurlisa Fahriani, Analysis of the Effectiveness of Crossing Bridges (JPO) in Samarinda City (Case Study Section Roads Ir. H. Juanda Samarinda).Supervised by Dr. Ir. H. Habir, MT and Ir. Eswan, ST., MT.The crossing bridge is one of the facilities provided for pedestrians, especially for those who will cross. The facility road due to footsteps, because pedestrians are compared to. But th reality on the ground shows that there are still many pedestrians when going across the road completely ignoring whereas the bridge, bridge facilities are available for pedestrians who will cross the road safely.This research was carried out in the July of 2018 on Ir. H. Juanda Samarinda, White Water Village, Kecamatan Samarinda Ulu, East Kalimantan Province. This study uses primary data collection methods, namely by direct survey to the field and disseminating questionnaire data and secondary data by collecting population data and location data. The analysis used in this study is based on Guttman Scale analysis of each mode based on the use of modes which use pedestrian analysis that will cross the road safety.From the result of this study on pedestrian bridges for pedestrian users on the road Ir. H. Juanda Samarinda, obtained the level of conformity with the Guttman Scale method, namely the effectiveness of the bridge crossing standard of conformity point above 50% that is equal to 67,2% and the effectiveness of the crossing bridge is included as effective criteria. So that it can be said the opinion of respondents stated more agree with the existence of the bridge crossing facility and the opinion of respondents who stated that they did not agree with the existence of the crossing bridge facility which amounted to 32,8%.